Assessment of Imaging Performance and Accuracy for the Diagnostic Evaluation of Wilms Tumor in Kids in the ERA of Contrast Based CT Scan with Histopathological Correlation: A Study in Tertiary Care Hospital - Amirali, Ashraf; Darira, Jaideep; Pathan, Hina; Murtaza, Sorath; Irshad, Munaza (International Journal of Innovative Research in Medical Science, 2021)
The aim of the study is the assessment of accuracy for the diagnostic evaluation of Wilms tumor in the pediatric population in the era of contrast-enhanced CT scan using histopathology as a gold standard. Plain and contrast-enhanced abdominal Computed Tomography including pelvis and chest was performed in suspected patients with multiple axial sections with sagittal and coronal reconstructions. Patients were being followed, data was collected and recorded on proforma after histopathology. The patient's mean age for this study in years was 3.5 ± 1.2. Gender distribution showed 170 patients (54.6%) were male while the remaining 141 patients (45.33%) were female. Contrast-enhanced computed tomography showed sensitivity (90.36%), specificity (51.72%), diagnostic accuracy (72.34%), positive predictive value (68.18%), and negative predictive value (82.42%) confirmed on Histopathology as the gold standard. It is concluded from the results of this study that contrast-enhanced computed tomography proved high diagnostic accuracy positive predictive in the detection of Wilms’ tumor by taking histopathology as the gold standard.